Correlations between family history and cancer characteristics in 2256 breast cancer patients - Molino, A (Nature Publishing Group, 2004)
A comparison of 692 early invasive breast cancer with, and 1564 without, a family history of breast cancer showed that the former were younger at diagnosis (P=0.002), had smaller tumours (P=0.012), were more frequently oestrogen receptor positive (P=0.006) and diagnosed preclinically (P<0.001).